Expert Oracle Application Express - Gault, Doug; Gielis, Dimitri; DSouza, Martin; Hartman, Roel; Mattamal, Raj; Kennedy, Sharon; Kubicek, Denes; Hichwa, Michael; McGhan, Dan; Scott, John; Nielsen, Anton; Mignault, Francis; et al. (Apress : Imprint: Apress, 2015)
Expert Oracle Application Express, 2nd Edition is newly updated for APEX 5.0 and brings deep insight from some of the best APEX practitioners in the field today. You'll learn about important features in APEX 5.0, and how those can be applied to make your development work easier and with greater impact on your business. Oracle Application Express (APEX) is an entirely web-based development framework that is built into every edition of Oracle Database. The framework rests upon Oracle's powerful PL/SQL language, enabling power users and developers to rapidly develop applications that easily scale to hundreds, even thousands of concurrent users. APEX has seen meteoric growth and is becoming the tool of choice for ad-hoc application development in the enterprise. The many authors of Expert Oracle Application Express, 2nd Edition build their careers around APEX. They know what it takes to make the product sing-developing secure applications that can be deployed globally to users inside and outside a large enterprise. The authors come together in this book to share some of their deepest and most powerful insights into solving the difficult problems surrounding globalization, configuration and lifecycle management, and more. New in this edition for APEX 5.0 is coverage of Oracle REST Data Services, map integration, jQuery with APEX, and the new Page Designer. You'll learn about debugging and performance, deep secrets to customizing your application user interface, how to secure applications from intrusion, and about deploying globally in multiple languages. Expert Oracle Application Express, 2nd Edition is truly a book that will move you and your skillset a big step towards the apex of Application Express development.